Bodyweight exercises & fitball / Patricia Pawa Patil ... [et al.] - Patil, Patricia Pawa; Nikol, Luke; Jemat Anchang, Gordon Nicolaus; Appukutty, Mahenderan (UiTM Press, 2024)
Regular physical activity is vital for promoting health and overall fitness level of people of all ages. One's power, stability and balance can be developed through regular fitness training. This book explains how to use bodyweight exercises for improving the core muscles, balance and body posture. Fitball is also helpful for exercise training, make it easier and feasible to perform at anytime and anywhere. Both approaches are easier and feasible to perform at any place (house, office or outdoor). Clear instructions and informative illustrations on how to perform the effective bodyweight exercises makes this book easy to use. We hope that with the contents and illustrations on how to perform the exercises with the correct techniques, this book suitable for everyone to use will be a reference and guidance to perform a correct technique of exercises, suitable for any group of populations; young, old, athletes or recreational and others.